2021
DOI: 10.1371/journal.pone.0258309
|View full text |Cite
|
Sign up to set email alerts
|

Shock propagation channels behind the global economic contagion network. The role of economic sectors and the direction of trade

Abstract: Examining the spread of macroeconomic phenomena between countries has become increasingly popular after the 2008 economic crisis, but the recent COVID-19 pandemic rendered this issue much more relevant as it shed more light on the risks arising from strongly interconnected economies. This paper intends to extend previous studies in this line by examining the relationship between trade openness and business cycle synchronization. It extends the scope of previous analyses in three areas. First, we use a Granger-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…The cascading effect in global trade networks has been studied extensively based on crossborder trade data [8][9][10][11]. When a failure occurs at one node in the network, it does not remain confined within that nation's borders, but extends to neighboring nodes.…”
Section: Introductionmentioning
confidence: 99%
“…The cascading effect in global trade networks has been studied extensively based on crossborder trade data [8][9][10][11]. When a failure occurs at one node in the network, it does not remain confined within that nation's borders, but extends to neighboring nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Our article also relates to the large literature on trade and shock propagation. Previous literature has shown that trade is a relevant channel for the propagation of macro shocks (for some relevant references, see Leila,, 2011; Beaudry et al., 2008; Hail & Pozo, 2008; Chang et al, 2022; Kali and Reyes, 2010; Iloskics et al., 2021). Trade integration can amplify local shocks but can also help dissipate impacts of adverse shocks (Chang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While this process undoubtedly brings efficiency and provides opportunities for developing countries to get involved in the global division of labour (Cristelli et al, 2015; Straka et al, 2017), the price that must be paid for these benefits is the systematic risk emerging from the increased interconnectedness (Barrot et al, 2020; Bonadio et al, 2021; Fang et al, 2020; Guan et al, 2020; He & Deem, 2010; Iloskics et al, 2021; Schweitzer et al, 2009; Sheng, 2010). Through the process of specialisation, the nodes and the edges of the global production network become increasingly exposed to certain disruptions, when adjustment of the supply chains requires longer periods of time.…”
Section: Introductionmentioning
confidence: 99%